Interface engineering of G-PEDOT: PSS hole transport layer via interlayer chemical functionalization for enhanced efficiency of large-area hybrid solar cells and their charge transport investigation. (1st November 2018) - Hilal, Muhammad; Han, Jeong In
Highlights: Simple fabrication technique approached for hybrid solar cells (O-IHSCs). The interface of G-PEDOT:PSS composite HTL chemically functionalized. It enhances the electrical conductivity of G-PEDOT:PSS 1 million (S/m). G-PEDOT:PSS composite HTL based O-IHSCs exhibit 3.90% of PCE. This Si/P3HT:PCBM/G-PEDOT:PSS interfaces may be recommended for commercial O-IHSCs. Abstract: In this study, in order to minimize the recombination current of free charge carriers in a large-area organic-inorganic hybrid solar cell (O-IHSCs), we improved the electrical conductivity of a graphene (G) and poly(3, 4-ethylenedioxy thiophene)–poly(styrenesulfonate) (G-PEDOT:PSS) hole transport layer (HTL) by introducing various concentrations of synthesized graphene (G) into poly(3, 4-ethylene dioxythiophene):poly(styrenesulfonate) (PEDOT:PSS). The electrical conductivity of G-PEDOT:PSS was enhanced to 932781.17 S m −1 via the addition of 2 mg/mL of G to PEDOT:PSS. The O-IHSCs fabricated with the highly conductive G-PEDOT:PSS composite as HTL enhanced the power conversion efficiency (PCE) to 3.90%, a 70% increase compared to O-IHSCs fabricated with pristine PEDOT:PSS HTL. However, the accumulation of G at a higher concentration (2.5 mg/mL) degrades the performance of the solar cell, which generated further defects or film aggregation, interfering with the fast transport of free charge carriers toward their respective electrodes. The G-PEDOT:PSS composite contained various types of functionalization via interfacial reaction between the G and PEDOT:PSS based on Raman and X-ray photoelectron spectroscopy studies. These chemical functionalizations provide an additional mechanism of charge transport via bridges enhancing the carrier mobility and suppression of recombination of free charge carriers, resulting in significant improvement in photovoltaic performance of the O-IHSCs.